Farm and family balance project: Evidence from Uganda - Ambler, Kate; Jones, Kelly M.; O'Sullivan, Michael (International Food Policy Research Institute, 2018)
This project tests two approaches to increasing women’s integration into and returns from cash crop value chains. We aim to determine whether these interventions affect intrahousehold allocation of resources, decision-making power, consumption and investment, productivity of the cash crop at the household level, and success of contract ful-fillment for the buyer of the crop.